The Effect of Work Environment and Training on Employee Performance with Mediation of Job Satisfaction Sandabi Group - Mohamad Zahri; Aryana Satrya; Rini Yayuk Priyati (Budapest International Research and Critics University, 2022)
The work environment (WE) and training (TD) can affect the performance (EP) and job satisfaction (JS) of employees, especially the Foremen and Clerks in the palm oil plantation Sandabi Group Bengkulu. To demonstrate this effect, researchers used a structured questionnaire as a survey method, and data from 156 persons Foremen and Clerks in 4 estates belonging to Sandabi Group were analyzed using the structural equation model. The results showed that the work environment has a positive and significant influence on performance through the mediation of job satisfaction. Likewise, training has a positive and significant influence on performance through the mediation of job satisfaction. The effect of job satisfaction can improve employee performance. This means that the improvement of employee performance in this case is the foreman and clerk can be achieved if the work environment policy continues to be improved or can be through increased employee job satisfaction. Furthermore, improved employee performance can be achieved if the training and development programs are implemented consistently or through increased job satisfaction of these employees. In the Anova test (different test), both the status of the employment relationship and the position contribute no different (the same), so it can be said that the contribution to performance is uninfluenced by the status and position of employees in this case are Foremen and Clerks.